Effect of opening on behaviour of the infilled frames with and without continuous lintel band - Singh P.K.; Singh V.; Yadav S. (My University, 2025)
In the past few decades significant amount of expermental work has been carried out in different parts of the world to understand the behaviour of infilled frames. But in the previous reported works on filled frames with opening, effect of lintel band over opening is not prperly covered. Objective of the present study was to understand behaviour of the brick masonry (BM) infilled reinforced concrete (RC) frame having shear connection between BM infill and the RC frame, and opening having isolated lintel and continuous lintel band. Three infilled frame models were tested for this purpose. The first model was BM infilled RC frame without opening. The second model was BM infilled RC frame with opening having continuous band. The third model was BM infilled RC frame with opening having isolated lintel. Shear connection between the enclosing frame and the infill was provided by the offsets in the alternate courses of the BM and casting the concrete after the BM was cast. Experimental results of the three types of frames under static loading were compared and it is concluded that due to higher load at first crack, more number of cracks at ultimate load, higher stiffness, strength and energy absorption capacity, the RC frame with opening having continuous lintel band was far more superior to infilled RC frame with opening having isolated lintel.